2006
DOI: 10.1038/sj.ki.5001869
|View full text |Cite
|
Sign up to set email alerts
|

BRAVO I: A pilot study of vascular brachytherapy in polytetrafluoroethylene dialysis access grafts

Abstract: Hemodialysis vascular access dysfunction owing to stenosis and thrombosis in polytetrafluoroethylene dialysis access grafts is a huge clinical problem for which there are currently no long lasting durable therapies. Vascular brachytherapy has been used successfully for the prevention of coronary restenosis following angioplasty and stent placement. The Beta Radiation for Treatment of Arterial-Venous Graft Outflow I study was a pilot study of vascular brachytherapy in hemodialysis patients with patent but dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…Endovascular brachytherapy and external radiation are additional interventional methods that have not yet been able to be proven to be superior and are thus not used in the clinical routine [69]. With the goal of preventing neointimal hyperplasia, brachytherapy was examined in a pilot study including 25 patients [15]. For ultrasound-guided PTA, there is currently only an insufficient number of studies of insufficient dialysis vascular access [70,71].…”
Section: Stenosis Of the Vascular Access Veinmentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular brachytherapy and external radiation are additional interventional methods that have not yet been able to be proven to be superior and are thus not used in the clinical routine [69]. With the goal of preventing neointimal hyperplasia, brachytherapy was examined in a pilot study including 25 patients [15]. For ultrasound-guided PTA, there is currently only an insufficient number of studies of insufficient dialysis vascular access [70,71].…”
Section: Stenosis Of the Vascular Access Veinmentioning
confidence: 99%
“…To prevent recurrent stenoses, the use of drug-coated balloons is increasingly being reported [12,13]. There are currently no randomized studies or even larger case series showing a superior long-term patency rate for endovascular brachytherapy [14,15] and cryoplasty [16]. In addition to thrombolysis via medication, thrombosed AV fistulas and vascular access grafts can be treated in a combined pharmacomechanical manner or purely mechanically with thrombectomy catheters [17] or hydrodynamic systems [18].…”
mentioning
confidence: 99%
“…How can the benefit of angioplasty be enhanced? A pilot study suggested that vascular brachytherapy increases the primary patency of grafts after angioplasty (83). Two retrospective studies suggested that stents, by creating a rigid scaffold for the vessel, prolong graft patency after thrombectomy and angioplasty (84,85).…”
Section: Mechanical Interventions To Reduce Graft Thrombosismentioning
confidence: 99%
“…At 1 year, the stenosis rate in the brachytherapy group was 56% compared with 37% in the control group (60). A multicenter clinical trial (Beta Radiation for Treatment of Arterial-Venous Graft Outflow) recruited 25 patients with a single stenosis at the vein-graft anastomosis of AVG for randomization to either radiation (18.4 Gy) after PTA or sham intervention after PTA alone (61). At 6 months, target lesion primary patency was significantly improved in the brachytherapy group (41.6% versus 0%; PTA alone); but 1-year thrombosis and patency rates were the same.…”
Section: Endovascular Approachesmentioning
confidence: 99%